Women entrepreneurs : making a difference - Bigelow, Pixie (New York, NY : Filmakers Library, 1998)
The focus of this documentary is the unique entrepreneurial qualities that women possess and the spirit with which they face the challenges of their personal and business lives. The four women profiled are Canadian, of different races, cultures and ages, and representing a cross section of businesses. All the women are self made; none have inherited their businesses. Starting with very little, their vision, their wits and their hard work have overcome setbacks and helped them keep going. There is a commonality among these women entrepreneurs in the way they manage their businesses, consider their employees as "family", reward hard work, and integrate their personal values into the corporate culture. The women are in disparate businesses. One turned a derelict hotel into a first class resort; one exports food to poor countries; one has an international software training company. The last runs a publishing empire from her home. Their businesses gross between one and twenty-seven million dollars. This documentary will dispell the myth that women entrepreneurs operate only small businesses, often in the retail sector, or cottage industries which are not regarded as serious business. It will be an inspiration to other women.
For High School; College; Adult audiences.
English.
Bronze Apple, National Educational Film & Video, 1998
CINDY Award Finalist, 1997
Print version record.
Keywords: Businesswomen -- Canada; Women-owned business enterprises; Entreprises appartenant à des femmes; women-owned business enterprises; Businesswomen; Women-owned business enterprises; Canada; Documentary; Streaming videos; Documentary